Promchanted - Matson, Morgan (Los Angeles ; New York : Disney-Hyperion, 2024)
Stella is obsessed with logistics and problem solving, and does not have time for fairy tales, but on a pre-prom visit to Disneyland she and Reece (a boy she accidentally got fired) get swept up in the world of Sleeping Beauty, and the girl who believes in logic, not fantasy, finds herself in a very illogical situation.
Keywords: Sleeping Beauty (Tale)--Adaptations--Juvenile fiction; Proms--Juvenile fiction; Fairy tales--Adaptations.; Dating (Social customs)--Juvenile fiction